Efektifitas Pelumasan Dalam Menurunkan Risiko Kerusakan Mekanis Pada Mesin Bubut - Bangun Subekti; Romiyadi Romiyadi; Yudi Dwianda (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
Lubrication plays a crucial role in maintaining the performance and reliability of lathes, particularly in mechanical systems operating under high pressure and friction. Without adequate lubrication, friction between metal components increases, leading to wear, excessive heat, and ultimately mechanical failures that can disrupt the continuity of production processes. This study aims to examine the effectiveness of lubrication in reducing the risk of damage to lathes, with a focus on the types of lubricants used, lubrication methods, and the frequency of their application. The research was conducted through a literature review approach, referring to various scientific and technical sources that discuss lubrication practices in the manufacturing industry. The findings indicate that an appropriate lubrication system can significantly extend the service life of machines, reduce maintenance costs, and improve operational efficiency. Therefore, a sound understanding of lubrication principles and practices is essential for comprehensive lathe maintenance.